Chronic Monoarthritis Pain Accelerates the Processes of Cognitive Impairment and Increases the NMDAR Subunits NR2B in CA3 of Hippocampus from 5-month-old Transgenic APP/PS1 Mice - Gong, Wei-Yi; Wang, Rong; Liu, Yuan; Jin, He; Zhao, Zhi-Wei; Wang, Yu-Lan; Li, Hong-Yan; Zhang, Xu; Ni, Jia-Xiang (Frontiers in Aging Neuroscience, 2017)
Many factors impact cognitive impairment; however, the effects of chronic pain and the mechanisms underlying these effects on cognitive impairment are currently unknown. Here we tested the hypothesis that chronic pain accelerates the transition from normal cognition to mild cognitive impairment in 5-month-old transgenic APP/PS1 mice, an animal model of Alzheimer’s disease, and that neurotoxicity induced by N-methyl-D-aspartic acid receptor (NMDAR) subunits may be involved in this process. Chronic monoarthritis pain was induced in transgenic APP/PS1 mice and 5-month-old wild-type mice by intra- and pre-articular injections of Freund’s complete adjuvant into one knee joint. Pain behavior, learning and memory function, and the distribution and quantity of NMDAR subunits (NR1, NR2A and NR2B) in hippocampal CA1 and CA3 regions were assessed. Our results showed that although persistent and robust monoarthritis pain was induced by the Freund’s complete adjuvant injections, only the transgenic APP/PS1 mice with chronic monoarthritis pain exhibited marked learning and memory impairments. This result suggested that chronic monoarthritis pain accelerated the cognitive impairment process. Furthermore, only transgenic APP/PS1 mice with chronic monoarthritis pain exhibited an overexpression of NR2B and an increased NR2B/NR2A ratio in the hippocampus CA3. These findings suggest that chronic pain is a risk factor for cognitive impairment and that increased neurotoxicity associated with NMDAR subunit activation may underpin the impairment. Thus, NMDARs may be a therapeutic target for the prevention of chronic pain-induced cognitive impairment.